2001
DOI: 10.1055/s-2001-12897
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Phylogeny of Nepenthaceae Based on Cladistic Analysis of Plastid trnK Intron Sequence Data

Abstract: Nepenthaceae are an exceptional family with regard to carnivory and the uniformity of characters. This makes it difficult to resolve phylogenetic relationships due to convergent evolution of morphological features. Using comparative sequencing of the chloroplast trnK intron, the monophyly of this complex family and hypotheses of infrageneric relationships were tested. Sequences from 71 Nepenthes taxa, representing all groups and two taxa of the closely related Ancistrocladaceae and Dioncophyllaceae as outgroup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
88
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(96 citation statements)
references
References 22 publications
6
88
2
Order By: Relevance
“…The sequences of N. albomarginata and N. alata were identical to those previously reported for the same species (Gene Bank accession numbers AF315908 and AF315891, respectively, Meimberg et al 2001). The sequence of the N. khasiana specimen (1,800 of 2,400 bp determined) was highly diverging from the published sequence of N. khasiana (Meimberg et al 2001).…”
Section: Dna Sequence Analysis Of the Nepenthes Species And Hybrids Umentioning
confidence: 65%
See 3 more Smart Citations
“…The sequences of N. albomarginata and N. alata were identical to those previously reported for the same species (Gene Bank accession numbers AF315908 and AF315891, respectively, Meimberg et al 2001). The sequence of the N. khasiana specimen (1,800 of 2,400 bp determined) was highly diverging from the published sequence of N. khasiana (Meimberg et al 2001).…”
Section: Dna Sequence Analysis Of the Nepenthes Species And Hybrids Umentioning
confidence: 65%
“…The sequences of N. albomarginata and N. alata were identical to those previously reported for the same species (Gene Bank accession numbers AF315908 and AF315891, respectively, Meimberg et al 2001). The sequence of the N. khasiana specimen (1,800 of 2,400 bp determined) was highly diverging from the published sequence of N. khasiana (Meimberg et al 2001). Instead, the N. "khasiana" specimen investigated here showed no diVerences to the sequences previously published for N. albomarginata and N. raZesiana (AF315908 and AF315910), indicating that it had been hybridized during cultivation.…”
Section: Dna Sequence Analysis Of the Nepenthes Species And Hybrids Umentioning
confidence: 65%
See 2 more Smart Citations
“…Therefore, Cenozoic dispersal was considered as a more plausible explanation than Mesozoic vicariance. A few similar debates exist in plants; for example, the oceanic dispersal versus Gondwana vicariance for the biogeography of the genus Adansonia (Baum et al, 1998), the circum-global dispersal versus Gondwana vicariance for the history of the family Melastomataceae , migration versus vicariance in Malpighiaceae (Davis et al, 2002a(Davis et al, , 2002b, the post-Gondwana longdistance dispersal versus Gondwana vicariance for the historical biogeography of the genus Polyscias (Plunkett et al, 2001), and the widespread-extinction hypothesis versus vicariance or long-distance dispersal theories for the history of the genus Nepenthes (Meimberg et al, 2001). Recently, Sanmartin and Ronquist (2004) also found that most of the plant patterns of suspected Gondwanan origin fit a dispersal rather than a vicariance scenario.…”
mentioning
confidence: 97%